Successful Pregnancy Outcome after Open Strassman Metroplasty for Bicornuate Uterus - Edgar Gulavi; Steve Kyende Mutiso; Charles Mariara Muriuki; Abraham Mukaindo Mwaniki (Hindawi Limited, 2018)
Introduction. Müllerian duct anomalies represent a group of congenital malformations that result from failure to complete bilateral paramesonephric duct elongation, fusion, canalization, or septal resorption. These anomalies are rare in the general population with a bicornuate or didelphys uterus being among the common ones. Bicornuate uterine malformations are of clinical significance due to their adverse reproductive outcomes. Metroplasty has been shown to improve reproductive outcomes of bicornuate uterine malformations. We document a case of bicornuate uterus that was managed with Strassman metroplasty and a subsequent successful pregnancy outcome. Case. A Black African lady was seen with a history of six prior miscarriages. Her diagnostic workup revealed a bicornuate uterus for which she had a Strassman metroplasty performed. She later conceived and was followed up to term with a successful live birth. Conclusion. Strassman metroplasty is a rare procedure in Sub-Saharan Africa and this case seeks to add to the body of knowledge on surgical management of Müllerian duct anomalies specifically bicornuate uterus in this region. This case report aims to increase the awareness of Müllerian duct abnormalities specifically bicornuate uterus in cases of recurrent miscarriages and highlight the diagnostic strategies to investigate and to demonstrate management options in low resource settings.